Impaired response of blood neutrophils to cell-death stimulus differentiates AQP4-IgG-seropositive NMOSD from MOGAD - Schroeder-Castagno, Maria; Del Rio-Serrato, Alba; Wilhelm, Andreas; Romero-Suarez, Silvina; Schindler, Patrick; Alvarez-González, Cesar; Duchow, Ankelien-Solveig; Bellmann-Strobl, Judith; Ruprecht, Klemens; Hastermann, Maria; Grütz, Gerald; Wildemann, Brigitte; et al. (Journal of neuroinflammation, 2022)
In neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD), neutrophils are found in CNS lesions. We previously demonstrated that NMOSD neutrophils show functional deficiencies. Thus, we hypothesized that neutrophil accumulation in the CNS may be facilitated by impairments affecting mechanisms of neutrophil death.
Gesehen am 06.12.2022